Pourquoi la Commission de la santé et de la sécurité du travail du Québec n’est pas le premier recours des enseignantes et des préposées à l’aide domestique ayant des lésions professionnelles - Nancy Guberman; Dominique Côté (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article examines the motives behind the decisions of two groups of workers on whether or not to submit claims to the Workers’ Compensation Board (CSST) for perceived work-related accidents or illnesses. It is based on qualitative interviews with 16 teachers and 16 cleaners. For both groups, motives for not making claims include the belief that the CSST is essentially for accidents and preventive work withdrawal for pregnant women, the view that compensation is difficult to obtain from the CSST, as well as a perceived difficulty of proving a relationship between their work and their health problem. For the cleaners, the difference between the compensation and employment income is also a factor, while for teachers, the fact that they have relatively easy access to wage-replacement insurance is one reason they do not submit claims to the CSST. To better understand the respondents’ choices, other factors such as their relationship to their job, their health, and their workplace culture must be taken into account.